An updated checklist of the herpetofauna of the Belum-Temengor forest reserves, Hulu Perak, Peninsular Malaysia - Amirah Hurzaid; Mohd A.A Bakar; Dionysius Sharma; Nurolhuda Nasir; Reuben Sharma; Ahmad R.Y. Aznan; Ibrahim Jaafar (Syiah Kuala University, 2013)
A herpetofaunal survey was carried out in Temengor Forest Reserve, Peninsular Malaysia during the second Temengor Scientific Expedition conducted from 1st to 10th October 2012. This study represents the first records of amphibians and reptiles of Sungai Enam Basin and an updated record of Belum-Temengor Forest Reserve. In this survey, a total of 27 species of herpetofauna was recorded comprising 12 species of amphibians from four families and 15 species of reptiles from six families. No new records of frog or lizard species are reported in this study. However, three new records of snakes are reported from the area.